Hydraulic and chemical properties of geosynthetic clay liners in mining applications - Conzelmann, Joel, author; Scalia, Joseph, advisor; Shackelford, Charles, committee member; Sutton, Sally, committee member (Colorado State University. Libraries, 2017)
Geosynthetic clay liners (GCLs) are thin (< 10 mm) factory manufactured hydraulic barriers used in environmental containment systems because of the propensity of bentonite to swell and immobilize water which results in low hydraulic conductivity, k (≤ 2-3×10-11 m/s). GCLs consist of bentonite (clay) bonded or sandwiched between layer(s) of geotextile and/or geomembrane. The effectiveness of GCLs in containment applications has been demonstrated for systems with low ionic strength solutions and leachates, such as municipal solid waste leachates. Increasingly, GCLs are being used in mining applications; these applications require further research and laboratory testing to demonstrate barrier effectiveness. Existing standard test methods are not well suited for testing of mine-waste-leachates; simple procedures to collect effluent for analysis are lacking, commercially available testing equipment is typically incompatible with extreme pH solutions often encountered, and the use of backpressure is recommended requiring testing at elevated pressures. To overcome these limitations, an alternative gravity method without backpressure, paired with a permeameter constructed from non-reactive materials and intended to minimize clogging was used. Validation of the gravity method is demonstrated through k and hydration testing with synthetic mine waste leachates and comparative tests performed by a standard method. Tests results support that GCLs attain saturation, and that the gravity method does not exhibit uncharacteristically low k due to unsaturated conditions. However, the gravity method revealed the possibility of preferential flow through fiber bundles for GCLs with higher degrees of needle punching which was not observed in standard method tests. The cause of the discrepancy between the two methods is hypothesized to be associated with applying backpressure in the standard method, indicating that the standard method may provide an un-conservative estimate of k for higher peel strength GCLs. Regardless, bentonite saturation is shown to occur without backpressure under conditions typical of k testing, illustrating that saturated (maximum k) tests can be achieved without backpressure. The k of GCLs to synthetic mine leachate solutions was tested using the gravity method with the chemical-resistant permeameter. Three different mine waste leachates are investigated, a neutral pH synthetic gold mining process solution, a high pH synthetic bauxite mining process solution, and a low pH synthetic copper mining process solution. Three different GCL products were also investigated, two higher peel strength GCLs (2170 N/m and 3500 N/m), and a standard peel strength GCL (700 N/m). The preliminary results of k testing are reported.